Truncating mutations in LRP4 lead to a prenatal lethal form of Cenani–Lenz syndrome. Issue 9 (12th June 2014) - Lindy, Amanda S.; Bupp, Caleb P.; McGee, Stephen J.; Steed, Erin; Stevenson, Roger E.; Basehore, Monica J.; Friez, Michael J.
<x xml:space="preserve">Abstract</x> Cenani–Lenz syndrome (CLS) is an autosomal recessive skeletal dysplasia that results in malformations of the distal limb, renal anomalies, and characteristic facies. In 2010, this condition was found to be caused by mutations in LRP4, a member of the low‐density lipoprotein family of receptors. LRP4 has been shown to antagonize LRP5/LRP6 activation of WNT and β‐catenin signaling. Loss of LRP4 function leads to excessive Wnt and β‐catenin signaling in the limb bud, which causes abnormal limb development. The large majority of patients with CLS reported in the literature have splicing and missense mutations, which result in syndactyly, oligodactyly, and minor renal malformations. More recently, a patient with CLS has been identified with a homozygous nonsense mutation and a more severe presentation of findings typically associated with this condition. Here we present two sibling fetuses with a prenatal lethal presentation of mesomelic limb reductions, oligosyndactyly, genitourinary malformation and compound heterozygosity for two novel truncating mutations in LRP4. These findings lend further support to the CLS genotype‐phenotype correlation presented in recent publications. © 2014 Wiley Periodicals, Inc.